Insights into setting time, rheological and mechanical properties of chitin nanocrystals- and chitin nanofibers-cement paste. (September 2022) - Haider, Md Mostofa; Jian, Guoqing; Zhong, Tuhua; Li, Hui; Fernandez, Carlos A.; Fifield, Leonard S.; Wolcott, Michael; Nassiri, Somayeh
Abstract: Chitin, the second most abundant biopolymer in nature, is available in the seafood industry's waste streams. In this pioneering study, chitin from waste shrimp shells was processed into chitin nanocrystals and nanofibers (Ch-NCs and Ch-NFs) for evaluation in the cement paste. The results show Ch-NCs delayed the final set time by up to 106 min, likely by electrostatic repulsion of cement particles, but Ch-NFs imparted only a max 78-min delay. Furthermore, the viscosity of fresh cement paste increased with Ch-NFs but did not significantly change with Ch-NCs. These different outcomes are attributed to more mobility of Ch-NCs rods versus the Ch-NFs network. In addition, nanochitin forms at 0.05 wt% of cement significantly increased 28d flexural strength by ∼40% and compressive strength by up to ∼12%. The encouraging results of this study indicate the promise of nanochitins in tailoring fresh and hardened properties of cement-based materials for target applications.